Pemerolehan Bahasa Anak Usia 3 Tahun di Paud Al-Anwar (Studi Kasus Muhammad Kaivan Arasyid) - Sri Wulan ebriyanti; Velayati Khairiah Akbar (Universitas Nias, 2023)
This study aims to describe the form of vocal and consonant acquisition in children aged 3 years in the case study of Muhammad Kaivan Arasyid. This study uses a qualitative descriptive research method. The theory used in this research is Darjowidjojo's theory (2012). The source of the data in this study was Kaivan's conversations of 3-year-old children at PAUD al-Anwar, where conversations were taken from parents, relatives, friends and teachers at school in the form of sentences that Kaivan often utters in everyday life. The results of the study concluded that the acquisition of the kaivan language obtained from the results of the study, that kaivan had acquired the vowel sounds (a), (i), (u), (e) and (0) clearly at the beginning, in the middle and at the end. kaivan has also acquired consonant sounds consisting of (b), (c), (d), (g), (h), (j), (k), (l), (m), (n), (p ), (s), (t), (w) and (y). there are several consonants that are difficult for kaivan to produce, namely consonants (f), (v), and (z) because when he reaches 3 years old, kaivan experiences loss of air which is still free due to the fact that his lower teeth are not perfectly attached to his upper lip. Meanwhile, the consonant (r) never appears at the beginning, in the middle or at the end, but removes and replaces the consonant (r) with (l). example: (walna) means (color)